Mualaf di Sabah: Kajian terhadap faktor peningkatan mualaf dan cabaran yang mereka hadapi - Zaifuddin Md Rasip; Issraq Ramli; Amer Hudhaifah Hamzah (Usuli Faqih Research Centre PLT, 2025)
Sabah, known for its diversity in ethnicity, culture, and religion, has experienced a significant increase in the number of Muslim converts (mualaf) over the past few decades. This study aims to investigate the factors driving the rise in the number of mualaf in Sabah and the challenges they face after embracing Islam. The research employs a qualitative design with a mixed-method approach, incorporating both quantitative and qualitative data analysis. Quantitative data were obtained from the registration records of mualaf provided by authoritative documents such as the Sabah Islamic Religious Affairs Department (JHEAINS) for the period from 2010 to 2023. Qualitative data, on the other hand, were collected through semi-structured interviews with mualaf. Data analysis involved thematic analysis to identify key themes related to the factors influencing conversion to Islam and the challenges faced by mualaf. The study identifies several key factors influencing individuals' decisions to convert to Islam, including exposure through media, dakwah programs, and social interactions with the Muslim community. It also evaluates the main challenges faced by mualaf, such as social adaptation, cultural conflicts, and family-related issues. The findings reveal a significant increase in the number of mualaf in Sabah, but they also highlight various challenges, including insufficient social support, difficulties in adapting to a new culture, and issues related to integration within the Muslim community. This study hopes to provide valuable insights for improving support systems and integration strategies for mualaf in Sabah, enabling them to fully embrace and practice Islamic teachings while serving as agents of Islamic outreach in the future